2002
DOI: 10.1128/jb.184.6.1722-1732.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rubredoxins Involved in Alkane Oxidation

Abstract: Rubredoxins (Rds) are essential electron transfer components of bacterial membrane-bound alkane hydroxylase systems. Several Rd genes associated with alkane hydroxylase or Rd reductase genes were cloned from gram-positive and gram-negative organisms able to grow on n-alkanes (Alk-Rds). Complementation tests in an Escherichia coli recombinant containing all Pseudomonas putida GPo1 genes necessary for growth on alkanes except Rd 2 (AlkG) and sequence comparisons showed that the Alk-Rds can be divided in AlkG1-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 45 publications
1
85
0
Order By: Relevance
“…Sequence alignments indicate that Rdxs involved in alkane oxidation fall into two classes, denoted AlkG1-and AlkG2-type Rdxs (9). RubA2 and RubA1 of P. aeruginosa PAO1 are both AlkG2-type Rdxs, are encoded by neighboring genes, and are 80% identical by amino acid sequence.…”
Section: Rdxr Discriminates Between Two Types Of Rdxmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence alignments indicate that Rdxs involved in alkane oxidation fall into two classes, denoted AlkG1-and AlkG2-type Rdxs (9). RubA2 and RubA1 of P. aeruginosa PAO1 are both AlkG2-type Rdxs, are encoded by neighboring genes, and are 80% identical by amino acid sequence.…”
Section: Rdxr Discriminates Between Two Types Of Rdxmentioning
confidence: 99%
“…Only the latter transfers electrons from RdxR to alkane hydroxylases (9). In AlkG1-type Rdxs, an additional arginine is inserted immediately downstream of the second metal-binding CXXCG motif.…”
Section: Rdxr Discriminates Between Two Types Of Rdxmentioning
confidence: 99%
See 1 more Smart Citation
“…Several rubredoxins from alkane-degrading bacteria have been cloned and analysed in complementation assays for their ability to substitute P. putida GPo1 AlkG. They clustered into two groups: AlkG1-type rubredoxins cannot transfer electrons to the alkane hydroxylase in GPo1, while AlkG2-type enzymes can do so and can substitute for AlkG [169]. AlkG1-type rubredoxins probably have…”
Section: Alkb In Pseudomonas Putida Gpo1mentioning
confidence: 99%
“…Previous studies showed that Acinetobacter sp. strain ADP1 requires at least five essential genes, namely rubA, rubB, alkM, alkR, and xcpR, for n-alkane utilisation (Ratajczak et al, 1998) confirming rubA, rubB, and alkM constitute a three component alkane hydroxyase system in A. calcoaceticus (Ratajczak et al, 1998;Geißdörfer et al, 1999;van Beilen et al, 2002). The overall alkR gene expression of LT 1 , samples was comparatively low in relation to the alkane hydroxylase complex genes, alkM and rubA.…”
Section: The Target Gene Expressions and Comparison Between Lt 1 And mentioning
confidence: 99%